An analysis of Korea's export performance using the constant market share model - Choi, Jong Hyub; Tang, John C.S.; Tabucanon, Mario T.; Vanchai Ariyabuddhiphongs; Government of Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1988)
During the past two decades Korea achieved a remarkable expansion in exports as well as in economic growth. The importance of exportand the acknowledged need to accelerate the process, however, raise the problem of providing analytical understanding of Korea's export performance. The objectives of this study is to assess the major determinants of export growth so that exporters and policy makers can appreciate the problems surrounding past export performance. Other possible sources of export growth such as productivity improvements and R&D expenditure are also examined. The Constant Market Share <CMS> model was adopted to assess the relative influence of various factors behind high export growth. Export growth factors by commodity groups and by market destinations are also examined by the transformed CMS model. Empirical results show that world demand increase and competitiveness effect were the main factors affecting Korean export growth in world markets during 1977- 1981 and 1981 - 1984 respectively. Result also shows that heavy and chemical products improved their competitiveness while simple labor-intensive products appeared to lose their competitiveness. It also shows the emergence of Asian countries as a potential market for Korean products. A notable suggestion is the improvements of competitiveness in major markets especially in the U. S. Possible sources of export growth especially with respect to competitiveness were examined. Results indicate that improvement of non - price competitiveness of exportable goods should be strengthened, and some price competitiveness such as productivity increase should also be pursued to maintain and increase Korea's export growth.
A Thesis Submitted in Partial Fulfilment of the Requirements for t he Award of the Degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1988
Keywords: Export marketing -- Korea